2009
DOI: 10.1002/0471142301.ns0528s46
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Novel Protein‐Protein Interactions Using Co‐Immunoprecipitation and Mass Spectroscopy

Abstract: Proteomics has evolved from genomic science due to the convergence of advances in protein chemistry, separations, mass spectroscopy, and peptide and protein databases. Where identifying protein-protein interactions was once limited to yeast two-hybrid analyses or empirical data, protein-protein interactions can now be examined in both cells and native tissues by precipitation of the protein complex of interest. Coupling this field to receptor pharmacology has recently allowed for the identification of proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 5 publications
0
70
0
Order By: Relevance
“…In this study, we aimed to gain more insights into the mechanism of action of LPPR1 by identifying the LPPR1-interacting proteins using affinity purification coupled to mass spectrometry (Berggard et al, 2007;Free et al, 2009). Surprisingly, we found that another three LPPR family members, LPPR3, LPPR4 and LPPR5, were associated with LPPR1.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aimed to gain more insights into the mechanism of action of LPPR1 by identifying the LPPR1-interacting proteins using affinity purification coupled to mass spectrometry (Berggard et al, 2007;Free et al, 2009). Surprisingly, we found that another three LPPR family members, LPPR3, LPPR4 and LPPR5, were associated with LPPR1.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the function of a protein in vivo, on the other hand, still requires a functional genomics approach involving detection of tissue-specific promoter activities, subcellular localization, possible post-translation modifications, and defining knock-outs or over-expressing mutants (Salzano and Crescenzi, 2005;Free et al, 2009). There are quite number of bioinformatics tools that can be used for in silico analysis of a protein to design a functional genomics approach (Table 1), thereby, in this manuscript we aimed to summarize online available tools for characterization of the protein of interest through in silico calculation of molecular weight and isoelectric point, detection of protein motifs and domains, estimation of subcellular localization and possible post-translational modifications.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial Hfq interacts with both A-rich mRNAs and uridine-rich (U-rich) sRNAs on opposite faces of the discshaped Hfq hexamer, referred to as the "distal" and "proximal" face, respectively [66]. The specific population of RNAs bound to Hfq can vary significantly between different homologs [12,28,67]. In terms of physiological effects, the Hfq protein decreases the rate of RNA turnover of bound RNAs and facilitates interactions between sRNAs and their target mRNAs.…”
Section: Hfq Is An Sm Protein: Structural Features and Implications Fmentioning
confidence: 99%
“…A second model suggests that RNA binds to two separate Hfq hexamers and interaction between the two hexamers facilitates annealing [67]. This model is partially supported by the crystal structure of AU 6 A with Hfq, which revealed the AU 6 A bound to the proximal face of one Hfq with the 5' adenosine docked to the distal face of another Hfq ring [82].…”
Section: Hfq Is An Sm Protein: Structural Features and Implications Fmentioning
confidence: 99%
See 1 more Smart Citation